Autism Functions/The Function of Autism - Stuart Murray (Disability Studies Quarterly, 2009)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:1; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 0 0 0 0 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:EN-GB; mso-fareast-language:EN-GB;} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> This article asserts that an idea of function is central to the loose public understanding of the ways in which autism is thought to operate in the world. It charts the multiple meanings of an idea of function and functioning across a number of examples–the early diagnostic writing of Leo Kanner and Hans Asperger, the subsequent development of their ideas in the formation of the languages of cognitive psychology and social psychiatry in which autism is discussed, and the languages of charities and foundations–before then looking at how this notion of function works in contemporary cultural/media moments. Here, the article uses two UK-based examples--a recent theatrical production of Rain Man in London and the reporting of the association between autism and crime--to argue that the notion of function is a fundamental and dangerous simplification of the ways in which autistic presence and intelligence actually manifest themselves.
Keywords: Autism; Function; Cultural Representation; Diagnostic Language; Media